The Effect of Work Facilities, Work Motivation and Education Level on Employee Performance at J&T Express Sampang (A Study at Four J&T Branches in Sampang Regency) - Gunawan, Hendra; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to examine the influence of work facilities, work motivation and level of education on employee performance. The approach used in this research is a quantitative approach. The sample used in this study was J&T employees in the Sampang area, Madura, East Java, totaling 60 respondents. Research data were obtained from the results of filling out questionnaires and analyzed using SEM analysis techniques with the help of the AMOS 22 program. The results of this study indicate that (1) work facilities have a positive and significant effect on employee performance; (2) Work motivation has a positive and significant effect on employee performance; (3) The level of education has a positive and significant effect on employee performance.